Care coordination for children with medical complexity. Issue 6 (June 2020) - Cady, Rhonda; Bushaw, Andrea; Davis, Heidi; Mills, Julie; Thomasson, Deana
Abstract : Abstract: Children with medical complexity have complex health management and care coordination needs. Care models that address these needs rely on interprofessional teams that include NPs. Understanding these care models allows NPs from all disciplines to support the care of this growing patient population in pediatric and adult settings. Abstract : Children with medical complexity have complex health management and care coordination needs. Care models that address these needs rely on interprofessional teams that include NPs. Understanding these care models allows NPs from all disciplines to support the care of this growing patient population in pediatric and adult settings.